On track or not? Projecting the global Multidimensional Poverty Index - Alkire, S; Nogales, R; Quinn, NN; Suppa, N (Elsevier, 2023)
This paper proposes a framework for modelling projections of multidimensional poverty. We use recently published repeated observations of multidimensional poverty, based on time-consistent indicators, for 75 countries. We consider and evaluate different approaches to model these countries’ trajectories of poverty reduction. Our preferred model respects theoretical bounds, is supported by empirical evidence, and ensures consistency of our main measure with its subindices. In our empirical analysis we first use this approach to assess whether countries are on track to halve poverty incidence between 2015 and 2030 if recent trends continue – 51 are – before assessing the reasonableness of this target. Subsequently, we discuss implications of our modelling framework for computing projections under sustained efforts, setting poverty reduction targets, and the evaluation of trajectory changes. These implications mainly follow from the bounded nature of our outcome variables and are, therefore, applicable to a wide array of development indicators.